Outpatient Follicle Monitoring: A Plea for Standardization in Ultrasound Based Follicle Monitoring and Data Transfer - M Murtinger; MH Zech; D Spitzer; NH Zech (JRI, 2014)
Background: The complexity of assisted reproductive technology (ART) increased during the last decades. New scientific and medical findings as well as the statutory requirements for improving the safety and the outcome of ART were the main impetus for its development. While therapy planning is done and ART is used by the IVF centers, the medical support and monitoring of patients is conducted by referring gynecologists. Reported follicle measurements by the gynecologist allow the adoption of the therapy plan. Most notably, the crucial aspect is processing and interpretation of ultrasound scan (US). The results of the received US, the transfer of data between IVF center(s) and referred physician(s) as well as the subjective interpretation often culminate in interpretation and logistical problems. This might increase the error probability with considerable detriments for the patients and ART outcome. Methods: The follicle monitoring was performed using Voluson I ultrasound system combined with SonoAVC® software. Results were communicated via DICOM language to DynaMed® software, a medical program for managing an IVF center with seamless integration of all processes needed for an accurate and precise workflow. Results: In this study, no loss of data was detected. All data were integrated by DynaMed® software and were recallable in a fast and easy manner. Conclusion: The broad usage of Voluson I ultrasound SonoAVC® software and communication of the results via Picture Archiving and Communication System (PACS) server between the IVF center and local gynecologist would provide more assistance for the patients and consequently the ART outcomes can be improved.